NORMALISASI UCAPAN KASAR DI MEDIA SOSIAL DALAM PERSPEKTIF PENDIDIKAN AKHLAK ISLAM - Siti Fadilah; Nafa Puspitarani; Ratna Khajar; Giyarsi; Adi Saputra (STKIP Subang, 2025)
The normalization of harsh and abusive language on social media has become a significant social phenomenon in contemporary digital communication. This study aims to analyze the normalization of offensive speech on social media from the perspective of Islamic moral education and to examine its implications for moral development, particularly among young users. This research employs a qualitative descriptive approach using library research as the primary method. Data were collected from books, scholarly journals, and credible digital sources related to Islamic ethics, moral education, and social media communication. The analysis was conducted through content analysis to identify patterns, themes, and moral implications of harsh language usage in digital spaces. The findings indicate that the normalization of abusive speech is influenced by the openness, anonymity, and rapid interaction patterns of social media, which gradually shift social norms and reduce sensitivity toward ethical communication. From the perspective of Islamic moral education, such practices contradict fundamental principles of akhlak, particularly the obligation to maintain respectful speech and self-control in communication. The study highlights the urgent need for strengthening Islamic moral education that emphasizes ethical digital communication, self-discipline, and moral awareness in social media usage. This research contributes theoretically to Islamic education studies by offering a moral framework for addressing communication challenges in the digital era.